Perbandingan Sikap dan Penerimaan Pengguna Layanan Dompet Digital di Indonesia - Anggraeni Dias Saputri; Ahmad Raf’ie Pratama (Jurnal KomtekInfo, 2021)
In Indonesia, the most commonly adopted electronic payment is an e-wallet. E-wallets have become a part of everyday life for Indonesians. Even so, there are not a few Indonesians who have not used this facility, the acceptance of e-wallets in Indonesia is still uneven. There are not a few studies that discuss e-wallets, however limited to research on acceptance without depending on other variables. Therefore this research was conducted to provide an overview of the comparison or differences in the attitudes of e-wallet users in Indonesia. The data obtained were analyzed quantitatively with Manova analysis technique. The findings of this study indicate that there are relatively no differences outside of two things, specifically the social influence in which women report higher scores than men. and on the perception of risk which is quite the opposite, that it was men who reported higher scores that were women. This research can complement and enrich the literature in the field of financial technology and provide an overview of the comparison or differences in attitudes of digital wallet services in Indonesia. In addition, the knowledge from this research is not only beneficial for digital wallet service providers, but widely for the financial technology industry.